Modified Burch Colposuspension – complex analysis of median term results of female stress incontinence with use subjective and objective diagnostic methods - Surkont, Grzegorz; Wlaźlak, Edyta; Stetkiewicz, Tomasz; Sobczuk, Anna; Krajewski, Paweł; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2005)
Specialists, who took part in II International Consultation on Incontinence in Paris in 2002 bought the idea, that there is big need to do prospective complex research to evaluate the most optimal use of diagnostic methods to diagnose women with SUI (stress urinary incontinence) before and after treatment. Aim of the study. This analysis refers to complex evaluation of medium term results of modified Burch colposuspension in treatment female SUI with use of few chosen subjective and objective diagnostic methods. Material and methods: We analyzed the results of first 50 colposuspensions provided by two gynecologic surgeons according to suggestions of prof. E. Petri from Germany. Results: We found big differences in percentage of cure women according to diagnostic method. Conclusions: 1. Methods of objective evaluation of female SUI symptoms have poor correlation to subjective methods. 2. To evaluate the results of female SUI treatment we should use a few subjective and a few objective methods. 3. There are differences in possibilities in obtaining data from patients depending on the diagnostic method.